2014
DOI: 10.1016/j.talanta.2014.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical immunosensor for the analysis of the breast cancer biomarker HER2 ECD

Abstract: a b s t r a c tHuman epidermal growth factor receptor 2 (HER2) is a breast cancer biomarker that plays a major role in promoting breast cancer cell proliferation and malignant growth. The extracellular domain (ECD) of HER2 can be shed into the blood stream and its concentration is measurable in the serum fraction of blood. In this work an electrochemical immunosensor for the analysis of HER2 ECD in human serum samples was developed. To achieve this goal a screen-printed carbon electrode, modified with gold nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 17 publications
2
65
0
Order By: Relevance
“…The affibody-HER2 affinity reaction was evaluated by injecting HER2 buffered solutions (prepared in 0.1 M PBS, pH 7.4) at different concentrations (20,30, 40 mg/L) and using 0.1 M PBS buffer pH 7.4 (added with 0.005% w/w Tween) as running buffer. All the measurements were performed at 25°C with the following experimental parameters: association phase 180 s, dissociation phase 180 s and flow 5 μL/min.…”
Section: Surface Plasmon Resonance (Spr) Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The affibody-HER2 affinity reaction was evaluated by injecting HER2 buffered solutions (prepared in 0.1 M PBS, pH 7.4) at different concentrations (20,30, 40 mg/L) and using 0.1 M PBS buffer pH 7.4 (added with 0.005% w/w Tween) as running buffer. All the measurements were performed at 25°C with the following experimental parameters: association phase 180 s, dissociation phase 180 s and flow 5 μL/min.…”
Section: Surface Plasmon Resonance (Spr) Measurementsmentioning
confidence: 99%
“…HER2 cancer biomarker was determined by DPV measurement in two linear ranges between 0.01 and 10 ng/mL and between 10 and 100 ng/mL. A sandwich based-immunoassay was proposed by Marques et al [30]; the immunosensor was assembled on the surface on AuNP modified graphite screen-printed electrodes, showing a linear range between 15 and 100 μg/L with a detection limit of 4.4 μg/L. An electrochemical aptasensor was described by Chun et al [31].…”
Section: Introductionmentioning
confidence: 99%
“…Human epidermal growth factor receptor 2 (HER2/neu, ErbB2 or CD340) is a key prognostic marker and an effective therapeutic treatment target for breast cancer that plays a major role in promoting breast cancer cell proliferation and malignant growth (Zhu et al, 2013); (Marques et al, 2014). This 185 kDa glycoprotein is overexpressed in around 20-25% of invasive breast cancers which is associated with poor-prognosis as well as reduced survival (Patris et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the established diagnostic methods, immunohistochemistry (IHC) and fluorescent in situ hybridization (FISH) for the assessment of ErbB2 status, are complex, involve time-consuming steps, require specially trained personnel and only provide semi-qualitative results, separating patients into ErbB2 -positive and ErbB2 -negative groups (Al-Khafaji et al, 2012); (Marques et al, 2014). Moreover, an in-depth analysis of the publications related to ErbB2 testing demonstrated that on average, 20% (range 10-40%) of the ErbB2-negative patients may be misclassified regarding ErbB2 status (∼2.5 million cases worldwide) and may develop a ErbB2-positive recurrent breast cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation